Delimitacja rekreacyjnej funkcji lasów i gospodarki leśnej na terenach zurbanizowanych - Gołos, Piotr; Zając, Stanisław (Leśne Prace Badawcze, 2011)
A method of assigning recreational function to forests is presented using the Warsaw agglomeration as an example for which natural and social characteristics have been specified. On the basis of an analysis and evaluation of the actual intensity of recreational use of forests within a distance of 100 kilometres from the capital city, four forest recreation zones were delimited. The limits of forest recreation zones in Warsaw and its surroundings were set based on; (1) the results of questionnaire surveys of a random, representative sample of 500 Warsaw residents (quantitative studies); (2) the conclusions formulated from studies focused on two age groups of Warsaw residents (qualitative studies); (3) data on the general characteristics of natural and social conditions in the forests; and (4) descriptions of the recreational qualities and conditions of communes. The main criterion for setting the locations and limits of forest zones (isoquants) was the actual level of recreational use of forests and the characteristic features of the major nonproductive functions of forest.